Using Microsoft Excel - Wilson, Kevin (Elluminet Press, 2023)
Unlock the full potential of Microsoft Excel with this comprehensive guide written by best-selling technology author and trainer Kevin Wilson. Whether you're beginning with the basics or an experienced user aspiring to enhance your skills, Using Microsoft Excel is your indispensable guide to navigating and mastering one of the world's leading spreadsheet applications. Using Microsoft Excel is packed with easy-to-follow instructions, full color illustrative photos, screenshots, and helpful tips, including video demos for a hands-on learning experience. In this guide you'll learn: User-Friendly Navigation: Start with the basics of the Microsoft Excel's interface and learn how to use the ribbon menu and backstage view. Spreadsheet Mastery: Learn how to create spreadsheets, manage data entry, and master text formatting. Stylish Data Presentation: Learn how to style and present your work in Microsoft Excel with sophisticated formatting options, borders, color-coding, and conditional formatting. Formulas and Basic Functions: Construct custom formulas and use built in functions to calculate, analyze, and transform your data. Advanced Excel Functions: Go beyond the basics with Lookup, Index, IF/Date/Text/nested functions, cell referencing and other advanced tools to streamline your data processing. Compelling Charts and Analytics: Transform data from Microsoft Excel spreadsheets into informative charts and master layouts to visually communicate your data. Efficient Workbook Management: Manage your Microsoft Excel environment effectively. Learn about file management and workbook navigation as well as printing and exporting worksheets. In-Depth Data Analysis: Explore advanced tools such as goal seek and scenarios for professional-level data analysis. As well as a look at the ToolPak and Solver add-ins. PivotTable Proficiency: Become adept at creating pivot tables and pivot charts for dynamic data breakdowns and insights. Excel Extensions: Extend the functionality of Microsoft Excel with various add-ins to meet your specific analytical needs. Macros & VBA Introduction: Step into the world of Macros and VBA to automate tasks and boost your productivity. Seamless Collaboration: Discover strategies for effective teamwork in Microsoft Excel with workbook sharing, real-time co-authoring and commenting. Flawless Data Validation: Ensure data integrity with various validation techniques, essential for accurate data management. This guide is an indispensable resource for learning the intricacies of Microsoft Excel, designed to enhance your abilities and provide you with the expertise necessary to craft professional-quality spreadsheets with ease. So scroll up and get your copy of Using Microsoft Excel today!